2012
DOI: 10.5230/jgc.2012.12.1.7
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Problem in Clinical Application of Sentinel Node Concept to Gastric Cancer Surgery?

Abstract: More than ten years have passed since the sentinel node (SN) concept for gastric cancer surgery was first discussed. Less invasive modified surgical approaches based on the SN concept have already been put into practice for malignant melanoma and breast cancer, however the SN concept is not yet placed in a standard position in gastric cancer surgery even after two multi-institutional prospective clinical trials, the Japan Clinical Oncology Group trial (JCOG0302) and the Japanese Society for Sentinel Node Navig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Moreover, a prospective multicenter clinical trial of a novel semi-automated molecular-based rapid diagnostic method for LN metastases using one-step nucleic acid amplification (OSNA) indicated that the method is feasible for intraoperative detection of LN metastases in patients with gastric cancer (Kumagai et al, submitted). Such new technology could overcome the difficulties of clinical application of the SN technique [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a prospective multicenter clinical trial of a novel semi-automated molecular-based rapid diagnostic method for LN metastases using one-step nucleic acid amplification (OSNA) indicated that the method is feasible for intraoperative detection of LN metastases in patients with gastric cancer (Kumagai et al, submitted). Such new technology could overcome the difficulties of clinical application of the SN technique [26]. …”
Section: Discussionmentioning
confidence: 99%
“…It has not been elucidated why this case only metastasized to the GNs; however, this suggests that it is crucial to limit SNNS to early gastric cancer. There has been some debate over the actual procedures for the clinical application of SNNS in gastric cancer, including the type of tracer to be used, the injection site, how to detect and harvest SNs and how to detect metastatic SNs (16). As regards the detection of metastatic SNs, researchers tend to focus on diagnostic methods, such as molecular techniques, rather than frozen section diagnoses with hematoxylin and eosin (H&E), which tend to be inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Japan Clinical Oncology Group (JCOG) also conducted a multicenter prospective trial of SN biopsy for cT1N0 gastric cancer [30]. The JCOG 0302 study was designed to assess the feasibility and accuracy of SN biopsy by the dye-guided method with intraoperative subserosal direct injection of ICG.…”
Section: Results Of Intraoperative Sn Mapping For Gastric Cancermentioning
confidence: 99%